The Danish High Risk and Resilience Study – VIA 7 - a cohort study of 520 7-year-old children born of parents diagnosed with either schizophrenia, bipolar disorder or neither of these two mental disorders. Issue 1 (December 2015) - Thorup, Anne; Jepsen, Jens; Ellersgaard, Ditte; Burton, Birgitte; Christiani, Camilla; Hemager, Nicoline; Skjærbæk, Mette; Ranning, Anne; Spang, Katrine; Gantriis, Ditte; Greve, Aja; Zahle, Kate; et al.
Abstract Background Severe mental illnesses like schizophrenia and bipolar disorder are known to be diseases that to some extent, but not entirely can be understood genetically. The dominating hypothesis is that these disorders should be understood in a neurodevelopmental perspective where genes and environment as well as gene-environment-interactions contribute to the risk of developing the disease. We aim to analyse the influences of genetic risk and environmental factors in a population of 520 7-year-old children with either 0, 1 or 2 parents diagnosed with schizophrenia spectrum psychosis or bipolar disorder on mental health and level of functioning. We hypothesize that a larger proportion of children growing up with an ill parent will display abnormal or delayed development, behavioural problems or psychiatric symptoms compared to the healthy controls. Methods/design We are establishing a cohort of 520 7-year-old children and both their parents for a comprehensive investigation with main outcome measures being neurocognition, behaviour, psychopathology and neuromotor development of the child. Parents and children are examined with a comprehensive battery of instruments and are asked for genetic material (saliva or blood) for genetic analyses. The participants are recruited via Danish registers to ensure representativity. Data from registers concerning social status, birth complications, somatic illnesses and hospitalization are included in the database. Psychological and relational factors like emotional climate in the family, degree of stimulation and support in the home and attachment style are also investigated. Discussion Data collection started January 1, 2013, and is successfully ongoing. By Aug 2015 424 families are included. About 20 % of the invited families decline to participate, equal for all groups.